SERVICE DELIVERY TERHADAP CUSTOMER VALUE SERTA DAMPAKNYA PADA KEPUASAN PELANGGAN - Galih Ginanjar Saputra; Undang Juju (Faculty of Economic and Business, University of Pasundan, 2020)
Satisfaction and dissatisfaction of customers to a product/service will affect the subsequent behavior patterns, and it is shown after the customers use of the product/service. The purpose of this reseacrh is to analyze the magnitude of influence service delivery towards customer value and the impact on customer satisfaction in Cuis Cake Cafe and Shop in Cianjur. The methods used in this reseacrh is explanatory survey methods, while for data analysis by using path anlysis. The results support four hypothesis are, an influence of service delivery to the customer value with the effect of 25,4%, the influence of customer value on customer satisfaction with the level of influence of 63,3%, the influence of service delivery to customer satisfaction with the level of influence of 28,9%, and an effect on the variable service delivery to customer value and impact to customer satisfaction with the overall level of influence of 66,9%. Keywords: Service Delivery; Customer Value, Customer Satisfaction